Students' Creative Thinking Ability in Solving Open-Ended Problems Based on Personality Type - Eys Arumningsih; Rina Dwi Setyawati; Yanuar Hery Murtianto (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
This study aims to determine the creative thinking ability of junior high school students in solving open ended problems in terms of students' different personality types. This type of research is descriptive qualitative with instruments in the form of Hippocrates - Galenus personality type questionnaire and written test of creative thinking ability on pythagorean theorem material. The subjects of this study consisted of 31 students of class VIII A of Walisongo 1 Semarang Junior High School. The results of this study showed that (1) the results of filling out the personality type questionnaire from 31 respondents obtained 29% of students with sanguinis personality type, 19% of students with choleric personality type, 23% of students with melancholic personality type and 29% of students with phlegmatic personality type. (2) subjects with melancholic personality type have high creative thinking ability, subjects with sanguinis and choleric personality type have moderate creative thinking ability, while subjects with phlegmatic personality type have low creative thinking ability. This study also shows that each student with a different personality type can affect the creative thinking ability of each student.